Methodological recommendations for practical classes in the discipline "Fundamentals of scientific researches" - Iershova, Natalia (Національний технічний університет "Харківський політехнічний інститут", 2023)
Modern institutional transformations in science as a sphere of human cognitive activity, awareness of tasks and functions of science, criteria for recognition of the results of scientific activity determine the need for improvement and further development of the process of scientific research, which ensures the formation of new scientific knowledge. An important direction of scientific activity is scientific research in higher educational institutions, which contribute to the formation of a qualitatively new content of the competencies of future specialists, and shape the intellectual potential of the country. The educational discipline "Fundamentals of scientific research" belongs to the professional disciplines of the master's training cycle in the specialty 071 "Accounting and taxation". Studying the organization of scientific research contributes to the deepening of the theoretical and practical abilities of an individual in accounting and taxation, who is able to work in the conditions of a market economy, that is, in those that require creative initiative, a high level of competence, and modern economic thinking. The subject of the academic discipline is scientific research. The goal of the educational discipline is for future specialists to master the theoretical foundations and acquire practical skills for conducting scientific research. At the same time, considerable attention is paid to the formation of students' skills in the use of scientific research methods, which creates significant competitive advantages among specialists of the economic profile in the labor market. The study of the discipline "Fundamentals of scientific research" is aimed at the formation of general and professional competencies of masters in the specialty 071 "Accounting and taxation". As a result of studying the discipline, the student should know: criteria for justifying the expediency of choosing a certain direction of scientific research; peculiarities of the definition and relationship between the object and the subject of 4 research; basic research methods and features of their application to solve certain tasks; substantive part of scientific research; the structure of a scientific article; requirements for the presentation of the results of scientific research. As a result of studying the discipline, the student should be able to: justify the problem of scientific research, its object and subject, navigate in the choice of an empirical base, methods of scientific generalizations; form conclusions and recommendations based on research results; conduct scientific research on the basis of developed theoretical foundations and methodology; to have tools for evaluating the effectiveness and efficiency of scientific activity; perform scientific works at the level of a diploma thesis, in accordance with the requirements for works of a similar level, from the moment of justifying the topic to public defense; prepare scientific articles as a form of approbation of the results of scientific research and their publication in collections of scientific works that have the status of professional publications. The purpose of this publication is to provide students studying in the specialty 071 "Accounting and taxation" with all the basic educational and methodological materials necessary for practical work in the course "Fundamentals of scientific research". The methodical guidelines contain control questions, tasks and exercises, the solution of which will help students thoroughly study the main topics of the course.
Keywords: methodological recommendations; scientific researches; practical classes; institutional transformations; scientific activity